Computerised Text Analysis Tools and Translation Quality. - Vermes, Albert (Eger Journal of English Studies, 2011)
This paper aims to show how computerised text analysis tools, along with the familiar word processing and spreadsheet applications, may aid the translator in identifying some key features of the source text before starting the translation and in producing and checking the target text. It is argued that such an approach may contribute to improving the quality of translations.